(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses one of the urgent tasks of the current higher education system - the formation of a specialist with professional and terminological competence. Opinions about independent education in the educational system, its role, place and importance in the educational process are presented. Information is presented on the organization of independent education in the credit-module system in higher education and the development of terminological competence in philology students through this process. Specific characteristics of independent work tasks are taken into account. The advantages of using the credit-module system in higher education are described and recommendations are given. By paying attention to independent education, the role and importance of philology students in the development of terminological competence is analyzed.